Interaction of brequinar and analogs with PD-L1: a molecular docking analysis - Gérard Vergoten; Christian Bailly (Exploration of Drug Science)
Aim: The immunosuppressive drug brequinar (BQR) is a potent inhibitor of dihydroorotate dehydrogenase (DHODH) active against autoimmune diseases and viral infections. This oral drug is currently evaluated for the treatment of cancers, notably acute myeloid leukemia to limit the suppressive function of myeloid cells. A combination of BQR and an anti-PD-1 (programmed death-1) antibody has revealed potent antitumor and antimetastatic activities. BQR induced a marked down-regulation of PD-L1 (programmed death-ligand 1) gene expression and a large decrease of PD-L1 protein expression in implanted tumors in mice. Methods: The present study evaluated the capacity of BQR to interact directly with the PD-L1 protein dimer using molecular modeling. Results: Molecular docking experiments revealed a modest capacity of BQR to stabilize PD-L1 dimers. The PD-L1 binding capacities of four known BQR analogs were compared to establish structure-binding relationships. The protein binding was significantly enhanced when the acid function of BQR was replaced with a trifluoroethanol substituent. The interaction was further reinforced when BQR was coupled to a mitochondria-targeted triphenylphosphine (TPP) unit. Among three BQR-TPP hybrids, compound B2 with a short alkyl linker revealed a prominent capacity to interact with PD-L1, superior to that of the reference biphenyl ligand BMS-202. Conclusions: Two PD-L1 binders derived from BQR have been identified and the protein interaction modeled. Our study underlines the possibility of designing novel small molecule ligands targeted to the PD-L1 dimer interface based on the BQR scaffold.